MEMAHAMI KARAKTER KEMISKINAN PERKOTAAN DENGAN PENDEKATAN OBSERVASIONAL - Yandri, Pitri; Juanda, Bambang (Jurnal Ekonomi & Studi Pembangunan, 2018)
Conceptually, there are many views in viewing the concept of poverty. So the issues may include social, economic, cultural and even political aspects. In spatial aspect, National Statistics Bureau (BPS) has also made distinctions between rural and urban poverty since 1999. This variance sometimes makes it difficult for undergraduate researchers to conduct an assessment of this issue. Therefore, this article attempts to analyze and strive to understand the character of urban poverty by using fourteen measures used by BPS. Fourteen indicators were then tested in the field using survey and observation methods. The results of the survey and observation are discussed further in this article